PAREPARE'S COMMUNICATION STRATEGY FOR RADIO ANNIVERSARY IN THE CHAPTER EVENTS PROGRAM Here and there (OBRAS) - Najib, Zulfajar (IAIN Parepare, 2021)
This study discusses the Communication Strategy of Intimate Radio Broadcasters in the Here-and-Side Chat Program (Obras). This study aims to determine the strategy, communication process, and the existence of an intimate radio broadcaster in Parepare City. This study is a qualitative study using theoryHypodermic (Syringe) as a way to see the process of the message content of the Chat Here and there (Obras) live, fast and have a strong effect on interest in hearing the program, as well as using theory Agenda Setting Theory which explains the cumulative effect of the media. The sources of data for this study are community leaders, loyal listeners of intimate radio, and the government. Data collection methods used in this study are observation, interviews, and documentation. The data processing technique used is the inductive method. The results of this study indicate that 1) The broadcaster's communication strategy carried out by Radio Mesra Parepare is to pay attention to the strengths, weaknesses, opportunities and threats which then emerges from the analysis that there is a broadcaster's communication strategy which is divided into 5 aspects, namely idea communication strategy, personality communication, personality projection, pronunciation strategies, and voice control strategies; 2)Based on the results of the study, it was concluded that the implementation of the communication strategy of Radio Mesra Parepare broadcasters in the Obrass program in general had gone well, including the use of fluent language, broadcasters focused on the material presented, and they had also used expression tools to support their communication. Each of the Obrass broadcasters has also had a different personality from one another, being friendly both when broadcasting and outside the broadcast, has been quite successful in pronunciation and generally has been able to control the voice when broadcasting.